Electrochemically driven polycrystallization of SnO2 nanobelts - Choi, HJ; Seong, HK; Park, JH; Park, JG; Cho, BW (ELSEVIER SCIENCE BV, 2004)
We report the conversion of one dimensional (ID) single crystalline SnO2 nanobelts into 1D polycrystalline nanobelts by intercalation of Li. Much improved electrochemical behavior of these 1D superstructures was observed due to "synergy" effect of high surface area and high electrochemical activity of 1D and zero dimensional (OD) structures, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: LITHIUM-ION BATTERIES